Furrow design for improving crop establishment of two-wheel tractor operated strip tillage planters in loam and clay loam soils - Hoque, M. Arshadul; Hossain, M. M.; Ziauddin, A. T. M.; Krupnik, Timothy J.; Gathala, Mahesh K. (International Journal of Agricultural and Biological Engineering, 2021)
Conservation agriculture (CA) based production systems may help in achieving more sustainable intensification of cropping systems that use less labour and energy and have higher profit margins, in addition to soil conservation and environmental impact mitigation advantages. But these objectives can only be achieved when the right mechanization options, including appropriate crop establishment equipment, are in place to assist in timely field operations. An urgent need exists, therefore, to fine tune and re-adjust the existing two-wheel tractor (2WT) operated seed drills, with specific reference to the design of blade and furrow openers, while at the same time considering performance in different soil types and environments. To this end, experiments were conducted during 2013-2014 and 2014-2015 at two BARI Regional Agricultural Research Stations in Jamalpur and Barisal, Bangladesh, on a loam and clay loam soil, respectively, to evaluate five types of furrow opener for strip tillage. Shoe and modified shoe-type furrow openers were tested and compared with three inverted-T furrow openers with rake angles of 75°, 65° and 55°. The newly designed inverted-T furrow openers were narrower than the shoe-type openers; they also had a longer, hollow shanks and provided better options for adjustment to achieve the desired seeding depth and line spacing. Compared to shoe-type openers, better seeding depth, uniformity and higher degree of seed coverage were recorded with use of the inverted-T furrow opener with a 65° rake angle. This resulted in better seed coverage in the furrow, a higher emergence rate index, and the highest emergence percentage of maize and mung bean. Our research findings can be generalized to smallholder production systems on loam and clay loam soils where farmers utilize 2WT operated seed drills for crop establishment in both traditional and conservation agriculture-based planting systems.Keywords: two-wheel tractor, strip tillage planter, inverted-T furrow opener, rake angle, conservation agriculture, emergence percentageDOI: 10.25165/j.ijabe.20211403.5906Citation: Hoque M A, Hossain M M, Ziauddin A T M, Krupnik T J, Gathala M K. Furrow design for improving crop establishment of two-wheel tractor operated strip tillage planters in loam and clay loam soils. Int J Agric & Biol Eng, 2021; 14(3): 130–139.